PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMPETENSI DAN KEPUASAN KERJA TERHADAP KINERJA - Mega Khairunnisa; Yumhi Yumhi; Ade Jaya Sutisna (E-Journal Studia Manajemen, 2020)
This study aims to obtain information regarding whether performance is influenced by transformational leadership, competence, and job satisfaction. Using a causal study through a survey at PT. Bank Rakyat Indonesia (Persero), Tbk Branch Office Pandeglang, for a sample of 50 employees, data for each variable was collected separately by respondents who filled out a questionnaire. The method used in this research is quantitative survey method, while the analysis technique used is path analysis using correlation and regression.The results prove that there is an effect of transformational leadership on performance, there is an influence of competence on performance, there is an effect of job satisfaction on performance, and there is an influence of transformational leadership, competence and job satisfaction together on performance.These findings indicate that organizations need to consider transformational leadership variables, competence, and job satisfaction in human resource planning and development at PT. Bank Rakyat Indonesia (Persero), Tbk Branch Office Pandeglang.